MRI bone oedema is the strongest predictor of subsequent radiographic progression in early rheumatoid arthritis. Results from a 2-year randomised controlled trial (CIMESTRA). Issue 3 (3rd April 2008) - Hetland, M L; Ejbjerg, B; Hørslev-Petersen, K; Jacobsen, S; Vestergaard, A; Jurik, A G; Stengaard-Pedersen, K; Junker, P; Lottenburger, T; Hansen, I; Andersen, L S; Tarp, U; et al.
Abstract : Objective: To identify predictors of radiographic progression in a 2-year randomised, double-blind, clinical study (CIMESTRA) of patients with early rheumatoid arthritis (RA). Methods: Patients with early RA (n = 130) were treated with methotrexate, intra-articular betamethasone and ciclosporin/placebo-ciclosporin. Baseline magnetic resonance imaging (MRI) of the wrist (wrist-only group, n = 130) or MRI of wrist and metacarpophalangeal (MCP) joints (wrist+MCP group, n = 89) (OMERACT RAMRIS), x -ray examination of hands, wrists and forefeet (Sharp/van der Heijde Score (TSS)), Disease Activity Score (DAS28), anti-cyclic citrullinated peptide antibodies (anti-CCP), HLA-DRB1-shared epitope (SE) and smoking status were assessed. Multiple regression analysis was performed with delta-TSS (0–2 years) as dependent variable and baseline DAS28, TSS, MRI bone oedema score, MRI synovitis score, MRI erosion score, anti-CCP, smoking, SE, age and gender as explanatory variables. Results: Baseline values: median DAS28 5.6 (range 2.4–8.0); anti-CCP positive 61%; radiographic erosions 56%. At 2 years: DAS28 2.0 (0.5–5.7), in DAS remission: 56%, radiographic progression 26% (wrist+MCP group, similar for wrist-only group). MRI bone oedema score was the only independent predictor of delta-TSS (wrist+MCP group: coefficient = 0.75 (95% CI 0.55 to 0.94), p<0.001; wrist-only group: coefficient = 0.59 (95% CI 0.40 to 0.77), p<0.001). Bone oedema score explained 41% of the variation in the progression of TSS (wrist+MCP group), 25% in wrist-only group (Pearson's r  = 0.64 and r  = 0.50, respectively). Results were confirmed by sensitivity analyses. Conclusion: In a randomised controlled trial aiming at remission in patients with early RA, baseline RAMRIS MRI bone oedema score of MCP and wrist joints (and of wrist only) was the strongest independent predictor of radiographic progression in hands, wrists and forefeet after 2 years. MRI synovitis score, MRI erosion score, DAS28, anti-CCP, SE, smoking, age and gender were not independent risk factors. Trial registration number: NCT00209859.